Combining Bimetallic-Alloy with Selenium Functionalized Carbon to Enhance Electrocatalytic Activity towards Glucose Oxidation. (1st August 2017) - Wang, Wei; Dong, Yinjuan; Xu, Li; Dong, Wenkui; Niu, Xiaobo; Lei, Ziqiang
Graphical abstract: Highlights: Novel Se-functionalized Se-C support is developed. Synergy exists between Se-C support and Pd3 Sn alloy NPs. Obtained Pd3Sn/Se-C has favorable GOR performance. Abstract: To combine with the advantages of selenium functionalized carbon and bimetallic-alloy nanoparticles (NPs), a novel Se-C supported Pd3 Sn (Pd3 Sn/Se-C) electrocatalyst was successfully prepared and estimated towords glucose oxidation reaction (GOR) in alkaline medium. The results demonstrate that Pd3 Sn/Se-C electrocatalyst possesses superior catalytic performance towards GOR. Specifically, it presents larger electrochemically active surface area, higher electrocatalytic activity and better cycling stability compared to those of Pd3 Sn/C, Pd/Se-C and Pd/C. This satisfactory result mainly owes to the special properties of Se-functionalized carbon material, as well as the synergetic effect between Pd3 Sn NPs alloy and Se-C support. Additionally, the effects of the concentration of electrolyte and glucose as well as the temperature on the activity for GOR have been investigated. This work will shed new light on the investigation of excellent Se-functionalized-support based electrocatalysts in the future.